Perspectives on Deprescribing in long-term care: qualitative findings from nurses, aides, residents, and proxies - Milta O. Little; Emily J. Hecker; Cathleen S. Colon-Emeric; Laurie Herndon; Eleanor S. McConnell; Tingzhong Michelle Xue; Sarah D. Berry (BMC, 2023)
Abstract Background Deprescribing initiatives in the long-term care (LTC) setting are often unsuccessful or not sustained. Prior research has considered how physicians and pharmacists feel about deprescribing, yet little is known about the perspectives of frontline nursing staff and residents. Our aim was to elicit perspectives from LTC nursing staff, patients, and proxies regarding their experiences and preferences for deprescribing in order to inform future deprescribing efforts in LTC. Methods This study was a qualitative analysis of interviews with nurses, nurse aides, a nurse practitioner, residents, and proxies (family member and/or responsible party) from three LTC facilities. The research team used semi-structured interviews. Guides were designed to inform an injury prevention intervention. Interviews were recorded and transcribed. A qualitative framework analysis was used to summarize themes related to deprescribing. The full study team reviewed the summary to identify actionable, clinical implications. Results Twenty-six interviews with 28 participants were completed, including 11 nurse aides, three residents, seven proxies, one nurse practitioner, and six nurses. Three themes emerged that were consistent across facilities: 1) build trust with team members, including residents and proxies; 2) identify motivating factors that lead to resident, proxy, nurse practitioner, and staff acceptance of deprescribing; 3) standardize supportive processes to encourage deprescribing. These themes suggest several actionable steps to improve deprescribing initiatives including: 1) tell stories about successful deprescribing, 2) provide deprescribing education to frontline staff, 3) align medication risk/benefit discussions with what matters most to the resident, 4) standardize deprescribing monitoring protocols, 5) standardize interprofessional team huddles and care plan meetings to include deprescribing conversations, and 6) strengthen non-pharmacologic treatment programs. Conclusions By interviewing LTC stakeholders, we identified three important themes regarding successful deprescribing: Trust, Motivating Factors, and Supportive Processes. These themes may translate into actionable steps for clinicians and researchers to improve and sustain person-centered deprescribing initiatives. Trial registration NCT04242186